60 Cardiogoniometry vs the 12-lead electrocardiogram at identifying the culprit lesion in patients with with non-st segment elevation myocardial infarction: the cognition study. (5th June 2017) - I Brown, Oliver; Davison, Benjamin; Rossington, Jennifer A; Clark, Andrew L; Hoye, Angela
Abstract : Introduction: Cardiogoniometry (CGM) is a method of 3-dimensional electrocardiographic assessment which provides detailed spatial and temporal information about cardiac electrical activity. The 12-lead electrocardiogram (ECG) is instrumental at localising ischaemia in patients with ST-elevation myocardial infarction, however ECG changes in non-ST elevation myocardial infarction (NSTEMI) are often non-specific for an ischaemic territory. The aim our our study was to evaluate the ability of CGM to identify the culprit lesion in patients with NSTEMI Methods: At a tertiary cardiology centre, patients with a diagnosis of NSTEMI were consecutively recruited in a prospective, double blind, observational study. CGM and 12-lead ECG recordings were performed prior to coronary angiography and were interpreted by independent investigators, with the location of the culprit lesion indicated by each recording recorded. Based on coronary angiography, the site of the culprit lesion was then determined by the operating interventionist. Measures of diagnostic performance were than calculated for CGM and the 12-lead ECG for each lesion site: left anterior descending (LAD), left circumflex (LCx) and right coronary (RCA). Kappa statistic for agreement was calculated between CGM, 12-lead ECG and coronary angiography. Results: Thirty patients (aged 67.5±10.8; 76.9% male) were recruited. Markers of diagnostic performance are shown in the table. Both CGM and the 12-lead ECG were able to provide ischaemia localising information in 57.7% of participants. Conclusion: Although CGM is superior to the 12-lead ECG at accurately locating the culprit lesion site in patients with NSTEMI, it is only able to provide ischaemia localising information in a similar number of patients as the 12-lead ECG.